Accurate vertical ionization energy and work function determinations of liquid water and aqueous solutions. Issue 31 (14th July 2021) - Thürmer, Stephan; Malerz, Sebastian; Trinter, Florian; Hergenhahn, Uwe; Lee, Chin; Neumark, Daniel M.; Meijer, Gerard; Winter, Bernd; Wilkinson, Iain
Abstract : A generalised liquid-phase photoelectron spectroscopy approach is reported, allowing accurate, absolute energy scale ionisation energies of liquid water and aqueous solutions, as well as liquid water's work function to be reported. Abstract : The absolute-scale electronic energetics of liquid water and aqueous solutions, both in the bulk and at associated interfaces, are the central determiners of water-based chemistry. However, such information is generally experimentally inaccessible. Here we demonstrate that a refined implementation of the liquid microjet photoelectron spectroscopy (PES) technique can be adopted to address this. Implementing concepts from condensed matter physics, we establish novel all-liquid-phase vacuum and equilibrated solution–metal-electrode Fermi level referencing procedures. This enables the precise and accurate determination of previously elusive water solvent and solute vertical ionization energies, VIEs. Notably, this includes quantification of solute-induced perturbations of water's electronic energetics and VIE definition on an absolute and universal chemical potential scale. Defining and applying these procedures over a broad range of ionization energies, we accurately and respectively determine the VIE and oxidative stability of liquid water as 11.33 ± 0.03 eV and 6.60 ± 0.08 eV with respect to its liquid-vacuum-interface potential and Fermi level. Combining our referencing schemes, we accurately determine the work function of liquid water as 4.73 ± 0.09 eV. Further, applying our novel approach to a pair of exemplary aqueous solutions, we extract absolute VIEs of aqueous iodide anions, reaffirm the robustness of liquid water's electronic structure to high bulk salt concentrations (2 M sodium iodide), and quantify reference-level dependent reductions of water's VIE and a 0.48 ± 0.13 eV contraction of the solution's work function upon partial hydration of a known surfactant (25 mM tetrabutylammonium iodide). Our combined experimental accomplishments mark a major advance in our ability to quantify electronic–structure interactions and chemical reactivity in liquid water, which now explicitly extends to the measurement of absolute-scale bulk and interfacial solution energetics, including those of relevance to aqueous electrochemical processes.